Note preliminaire sur l'embouche de bovins Kouri dans la region du lac Tchad - Tacher, G. (1974)
Performance of Kuri on supplementary feeding is investigated. Fattening of Kouri cattle using cottonseed and forage crops (Pennisetum purpureum and its varieties) in the lake Chad region was examined. Data on feeding levels and animal responses in terms of weight gain included.